2018
DOI: 10.14358/pers.84.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Modeling of Soil Salinity Using WorldView-2 Data and EM38-KM2 in an Arid Region of the Keriya River, China

Abstract: Soil salinity is one of the common factors leading to land degradation problems on earth, especially in arid and semiarid regions. There is an urgent need for rapid, accurate and cost-effective monitoring and assessment of soil salinization. Remote Sensing (<small>RS</small>) and Geographical Information Systems (<small>GIS</small>) are employed as viable technologies for detecting, monitoring, and predicting spatial-temporal patterns of soil salinization. The purpose of this study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…In addition, the spatiotemporal dynamic nature of soil salinity makes it very difficult to use conventional methods for comparisons over large territory [5]. Several authors have examined the advantages of remote sensing methods and sensors for the assessment of soil degradation due to salinity [1, [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Remote sensing methods are relatively easy to apply and reliable in certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spatiotemporal dynamic nature of soil salinity makes it very difficult to use conventional methods for comparisons over large territory [5]. Several authors have examined the advantages of remote sensing methods and sensors for the assessment of soil degradation due to salinity [1, [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Remote sensing methods are relatively easy to apply and reliable in certain conditions.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of the hyper dry arid climate, geomorphological, soil formation conditions, and shallow groundwater levels facilitated the movement of dissolved salts to the land surface. Our research team also did some study on soil salinity detection and maps on the Keriya River site [16,17]. We found that such phenomena caused soil salinization and desertification, especially in the transitional belt between the oasis and the desert.…”
Section: Introductionmentioning
confidence: 90%
“…The Keriya River is located in the southern part of the Taklamakan Desert in the Xinjiang Uyghur Autonomous Region of China [17,18]. This river originates from the Kunlun Mountains and flows through the Keriya Oasis, and after approximately 700 km, the river ends in the hinterland of the Taklamakan Desert [18].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations